HIDROGEOCHEMISTRY STUDY TO DETERMINE GENESIS OF ACID WATER IN LINAU LAKE, NORTH SULAWESI - AMBASSADUR SHIDDIQ (NIM : 32008005); Tim Pembimbing : Prof. Ir. Lambok M. Hutasoit, M.Sc., , JULIAN
Acid water is one of the problems that typically occurs in a geothermal field associated with volcanic activity process because it corrodes metal based materials. Determination of the origin of acid water and how the process of its formation are beginning to be examined in several geothermal fields in the world to overcome the negative impacts of the presence of this fluid. Lahendong geothermal field is one of the geothermal fields in Indonesia, which has acid water that is present in the reservoir and on the surface in the form of the acid crater lake. The objective of this study is to determine how the water of Linau Lake acid to formed, the relationship between the water in the Linau Lake with acid water in the reservoir and process of its formation. Research hypothesis is that Linau Lake water is derived from SO42- formed as the oxidation and hydrolysis of magmatic gases at shallow depth which and rises to the surface. This study carried out subsurface geology cross-sectional analysis, fluid geochemistry analysis from surface and wells, fracture and fault density analysis and water balance analysis. Subsurface geology cross-sectional analysis produces cross-sectional area of the research area to determine the effect of subsurface Lithology and geological processes on the formation of acid fluid. The Geochemical analysis were performed for water and gas composition from surface and wells, together with analysis of stable isotopes 18O and 2H and distribution pattern analysis of subsurface temperature. From the geochemical analysis is obtained the origin of fluid in the reservoir and the surface in the research area and geological processes that occurred since the entry of meteoric water in the catchment areas, into the reservoir until it appears on the surface. Analysis of fracture and fault density results in distribution map of fracture and fault density in the research area. Map of the results of the analysis of the distribution of fracture and fault density is used to create a zoning map from catchments areas result of stable isotope analysis.Potential evapotranspiration values are calculated in this study using a modified Penman equation. Determination of parameters of water balance models of NRECA in the research area are from the sub drainage area of Tondano due to the unavailability of sufficient data in the research area. From the results of the simulation are obtained correlation values between the simulated discharge and the measurement results is 72 %. Integration of the results of geochemical analysis of surface and well fluids, subsurface temperature distribution data and subsurface geology indicates that the acid in the study area is derived from SO42-. SO42- in the study area is from the condensation of magmatic gases into geothermal gases and mixed with groundwater at the depths below 1692 m and oxidation of H2S gas at shallow depths. Magmatic gases is part of the magma volatile off due to pressure drop whereas geothermal gases is gas produced by the condensation of magmatic gases due to temperature decreas. H2S oxidation occurred after H2S gas release from the liquid phase due to the boiling process that occurs when the geothermal fluid flows to the surface. Based on the chemical and physical composition of the reservoir and surface fluids, the temperature profile, morphology and geologic conditions it is concluded that the Linau Lake is a volcanic lake which is above an active crater. The results of the calculation of NRECA water balance models, using parameters of the simulation results of subdrainage area of Tondano, shows that the volume of meteoric water that enters the Linau Lake in 2008 - 2012 was 59.56 x 106 m3. From the results of calculation with chemical equation to calculate the pH of the solution and the data volume of meteoric water that enters the Linau Lake in 2008 - 2012 was 59.56 x 106 m3. From the results of calculation with chemical equation to calculate the pH of the solution and the data volume of water meteoric that went into the Linau Lake is obtained H2SO4 amount that goes into Linau Lake in 2008 to 2012 is 5.71 x 106 m3. The integration of infiltration distribution map based on stable isotopes 18O and 2H and distribution of fracture and fault map results in infiltration map. From the results of calculation using area of catchment zone fracture and fault density, hydrological model parameter's and meteorological parameters, the volume of meteoric water recharging into the geothermal system in 2008 - 2012 is 123.29 x 106 m3. This study is expected to provide new insights and understanding in understanding the process of the formation of acid water on volcanic lakes above the active crater and acidic water in geothermal reservoirs. This study is also expected to provide a new concept in calculating the amount of water infiltration into the geothermal system using stable isotopes (18O and 2H), fracture and fault density method and water balance method. Studies on the relationship between the volume of H2SO4 that went into the Linau Lake and production wells are expected to provide a better understanding of the influence of the production process of reservoir fluids to the formation of acid in Lahendong.geothermal field.